A self-cleaning and photocatalytic cellulose-fiber- supported "Ag@AgCl@MOF- cloth'' membrane for complex wastewater remediation. (1st November 2020) - Lu, Wanli; Duan, Chao; Liu, Chaoran; Zhang, Yanling; Meng, Xin; Dai, Lei; Wang, Wenliang; Yu, Hailong; Ni, Yonghao
Graphical abstract: Highlights: A self-cleaning and photocatalytic cellulose-supported hybrid membrane was fabricated. The as-prepared membrane exhibited robust oil/water separation and dye removal. Carboxymethylation improved the hydrophilicity of membrane and MIL-100(Fe) loading. The Ag@AgCl nano-photocatalyst enhanced the photocatalytic activity of membrane. Abstract: Membrane technology is one of the most promising technologies for wastewater remedy. However, it remains challenging to prepare high-performance membrane matrix for complex pollutants, e.g. containing both oil and organic dye. In this work, we facilely fabricate a cellulose-fiber-supported MOF photocatalytic membrane, namely Ag@AgCl@MIL-100(Fe)/CCF, which was prepared via carboxymethylation of cotton fabric (CCF) as scaffold and in-situ synthesis of MOF derivative as photocatalyst. The carboxymethylation significantly improves the hydrophilicity of cotton fabric and the deposition amount of MIL-100(Fe). The high hydrophilicity of modified CCF and porous MIL-100(Fe) further enable the membrane with an efficient adsorption capacity of dyes and underwater oleophobicity against oils. The photocatalysts Ag@AgCl nanoparticles anchored onto MIL-100(Fe) promote the photocatalytic activity. As a result, the membrane shows simultaneous high removal efficiency towards dyes (97.3 %) and oils (99.64 %). Additionally, thanks to the good photocatalytic activity against organic pollutants, the membrane exhibits excellent self-cleaning and a long-term reuse capacity.